Historical aspects of tourist development in the Chornohora massif of Ukrainian Carpathians - Ziuzin, Sviatoslav; Rozhko, Igor (Journal of Education, Health and Sport, 2019)
The paper highlights and analyzes the main stages of tourist development of the Chornohora massif of the Ukrainian Carpathians since the middle of the 19th century up to this day. It also describes the first tourist shelters created within the boundaries of Chornohora and the tourist associateons that contributed to the appearance of the first tourist infrastructure.